A strategic framework for technological innovations in support of the customer experience: A focus on luxury retailers. (May 2022) - Pantano, Eleonora; Pedeliento, Giuseppe; Christodoulides, George
Abstract: Luxury organizations have traditionally resisted technology, as they perceived it to be antithetical to the values of luxury. Recently, however, competitive and market pressures, compounded by the global pandemic, have prompted luxury organizations to utilize significant technological innovations to enhance their customer experience, mostly on an ad hoc basis. Across four case studies in the luxury fashion retail sector, we conduct 12 interviews with managers. This paper advances a framework that encourages luxury organizations to consider technological innovation in retailing from a strategic point of view. Such a view involves contemplating questions regarding what technology type to adopt (radical vs. incremental) and when the best timing is to adopt the technology (pioneering vs. following technological leaps). The framework identifies four retailer roles that emerge from the innovation process: facilitator, enabler, explorer, and initiator . Each role comprises a different set of risks, resource implications, and expected returns. Graphical abstract: Image 1